Note on decompositions based on the vertex-removing synchronised graph product - Antoon Hendrik Boode (Electronic Journal of Graph Theory and Applications (EJGTA), 2022)
Recently, we have introduced two graph-decomposition theorems based on a new graph product, motivated by applications in the context of synchronising periodic real-time processes. This vertex-removing synchronised product (VRSP) is based on modifications of the well-known Cartesian product and is closely related to the synchronised product due to Wöhrle and Thomas. Here, we show how we can relax the requirements of these two graph-decomposition theorems.